The Sinergy Aspects of the Contemporary Educational Process - V. A. Starodubtsev; O. M. Shepel; A. A. Kiseleva (Russian State Vocational Pedagogical University, 2015)
Using the comparative analysis method, the authors examine the evo- lutional process of the natural science methodology and the methodology of education. The outlined analogies show some definite trends of education development in the emerging post-industrial society. It is demonstrated that the openness and correlation of the individual educa- tional activities with other co-players results in the actual cooperation of the educa- tional process. According to the authors, the implementation ground for the distributed inter- actions in the virtual space of the Internet, capable of supporting the life long learning process of society members, should be the personal educational environment, as a part of global information environment; the former being developed and used by the individual both for personal professional realization and life-long continuing self- education.